D-BMAP18 Antimicrobial Peptide Is Active In vitro, Resists to Pulmonary Proteases but Loses Its Activity in a Murine Model of Pseudomonas aeruginosa Lung Infection - Mardirossian, Mario; Pompilio, Arianna; Degasperi, Margherita; Runti, Giulia; Pacor, Sabrina; Di Bonaventura, Giovanni; Scocchi, Marco (Frontiers in Chemistry, 2017)
The spread of antibiotic resistant-pathogens is driving the search for new antimicrobial compounds. Pulmonary infections experienced by cystic fibrosis patients are a dramatic example of this health-care emergency. Antimicrobial peptides could answer the need for new antibiotics but translating them from basic research to the clinic is a challenge. We have previously evaluated the potential of the small membranolytic peptide BMAP-18 to treat CF-related infections, discovering that while this molecule had a good activity in vitro it was not active in vivo because of its rapid degradation by pulmonary proteases. In this study, we synthesized and tested the proteases-resistant all-D enantiomer. In spite of a good antimicrobial activity against Pseudomonas aeruginosa and Stenotrophomonas maltophilia clinical isolates and of a tolerable cytotoxicity in vitro, D-BMAP18 was ineffective to treat P. aeruginosa pulmonary infection in mice, in comparison to tobramycin. We observed that different factors other than peptide degradation hampered its efficacy for pulmonary application. These results indicate that D-BMAP18 needs further optimization before being suitable for clinical application and this approach may represent a guide for optimization of other anti-infective peptides eligible for the treatment of pulmonary infections.